Dois modos de campo eletromagnético em cavidades dissipativas: coeficientes de dissipação cruzada e estados resistentes - Romeu Rossi Junior (2005)
We describe a feasible experiment sensitive to the magnitudes and phases of the cross decay rates in a system composed by two electromagnetic modes interacting with the same reservoir. We show that if the cross decay rates are appreciable there are states less exposed to decoherence and dissipation, and in limiting situations a decoherence free subspaces appears.